Siklus Kehidupan Kupu-Kupu Sebagai Inspirasi Penciptaan Seni Patung - Widi Apriana, I Wayan; Jodog , I Made; Mustika, I Ketut (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2022)
The life cycle of a butterfly in the Butterfly Park as an object of research on the creation of art works (sculptures), with the title “The Life Cycle of a Butterfly As Inspiration for the Creation of Sculpture Artwork.” To find out the problems faced by the author, it is necessary to research steps creation of works of art using construction theory approaches, semiotic theory, and aesthetic theory, while the research process uses a qualitative approach using data collection methods: observation, interviews, documentation, and literature study. The results of the discussion (1) the author makes with a representation of the butterfly’s life cycle, namely: (a) mating, (b) birth, (c) writhing (d) transitional period, and (e) rebirth. (2) in the process of carrying out the work using reinforced concrete materials with the technique of forming, sticking, adding and subtracting. (3) the embodiment of the author’s work displays a visual of the butterfly’s life cycle with a natural style in every work that is embodied. The color in each work that is realized by the author, namely the color of each object the is used as a reference for every three- dimensional artwork (sculpture). From this concept, a thesis work will be created. Five sculptures and journals.